EXPLORING STUDENTS' PERCEPTIONS OF GRAMMARLY AS A TOOL FOR ENHANCING GRAMMAR ACCURACY IN WRITING - Indiah Pane, Isli Iriani; Alvindi, Alvindi; Dimas, Dimas; Sadri, Idris (UIN Sumatera Utara, 2024)
Mastering the structural aspects of language is a crucial component of academic writing. However, students often make intentional or unintentional errors during the writing process due to a limited understanding of grammatical principles and conventions. Careful revision and editing are vital to minimizing these errors, but technological tools such as Grammarly have become popular aids for students in checking sentence structure and grammar. This study investigates students' perceptions of Grammarly, focusing on its perceived advantages and disadvantages as a grammar-checking tool. Employing a qualitative descriptive approach, data were collected through a questionnaire distributed to 25 students. The findings reveal that while Grammarly offers notable benefits, such as ease of use and immediate feedback, 89.5% of students identified limitations that reduce its effectiveness. Specifically, 50.8% of respondents highlighted disadvantages, whereas 45.5% acknowledged advantages. Additionally, 42.9% of students expressed mixed sentiments regarding Grammarly's overall utility. These findings provide insights into the nuanced role of Grammarly in supporting students' academic writing and highlight areas for improvement in its application.